2017
DOI: 10.7322/jhgd.127681
|View full text |Cite
|
Sign up to set email alerts
|

Growth and puberty in a prospective cohort of patients with sickle-cell anaemia: an assessment over ten years abstract

Abstract: Suggested citation: Gomes ICP, Melo HI, Melo SIA, Menezes NV, Dantas TVP, Cipolotti R. Growth and puberty in a prospective cohort of patients with sickle-cell anaemia: an assessment over ten years. J Hum Growth Dev. 2017; 7(1): 91-98 AbstractIntroduction: Hereditary haemoglobinopathies are the most common group of monogenic hereditary diseases in the world. Erythrocytes in sickle form, cellular expression of polymerization of deoxygenated HbS, cause intermittent vascular obstruction, leading to tissue ischaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The overall prevalence of sub-clinical hypothyroidism reported in the present study is within the range of 2 – 6% reported by previous researchers ( 8 , 26 , 27 ). On the contrary, this reported prevalence rate was lower to what Gomes et al ( 28 ) reported amongst thirty Brazilian children with sickle cell anaemia aged > 10 years. The observed difference is possibly an effect of the characteristics of the population studied.…”
Section: Discussioncontrasting
confidence: 86%
“…The overall prevalence of sub-clinical hypothyroidism reported in the present study is within the range of 2 – 6% reported by previous researchers ( 8 , 26 , 27 ). On the contrary, this reported prevalence rate was lower to what Gomes et al ( 28 ) reported amongst thirty Brazilian children with sickle cell anaemia aged > 10 years. The observed difference is possibly an effect of the characteristics of the population studied.…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, the group of patients with SCA had lower anthropometric indices than the control group, a finding related to weight and BMI in agreement with previous studies. 7,29 The findings of increased food intake and reduced anthropometric measurements support the hypercatabolic state of patients with SCA.…”
Section: Discussionmentioning
confidence: 81%
“…In the current issue of JHGD these studies evaluate technologies that involve the improvement of health conditions and/or issues for public health investigating the health situation of the population, especially children and adolescents [8][9][10] , which corroborate the themes in the health promotion field within the context of primary care focusing on teens and their vulnerabilities [11][12][13] , nutrition and influence on child and adolescent development [14][15][16][17][18] and themes focused on translational medicine, describing results to improve the health indicators of the population [19][20][21][22] . With an emphasis on nutritional status, to highlight obesity in adolescents, Tebar et al 17 found the prevalence of abdominal obesity in adolescents in the city of Londrina, Paraná, Brazil, and its associated factors.…”
mentioning
confidence: 81%
“…Also in this issue of evaluation of growth and development, Gomes et al 22 evaluated the pattern of growth and pubertal development of a group of patients with Sickle Cell Anaemia (SCA) from childhood to adulthood. Patients with SCA presented growth impairment and pubertal delay when compared to healthy controls.…”
mentioning
confidence: 99%